2016
DOI: 10.1186/s12933-016-0366-9
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of resveratrol and quercetin on in vitro-induced diabetic mouse corpus cavernosum

Abstract: BackgroundHyperglycemia and increased levels of methylglyoxal (MGO) can trigger the development of vascular complications in diabetes. Resveratrol and quercetin are red wine polyphenols with known beneficial cardiovascular properties, including an antioxidant capacity. This study evaluated whether resveratrol and/or quercetin could prevent in vitro-induced diabetic changes in neurogenic and vascular relaxant responses of mouse arteries and corpora cavernosa.MethodsIsometric tension of isolated aorta, mesenteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 47 publications
(78 reference statements)
1
13
0
Order By: Relevance
“…Furthermore, pretreatment of MAECs with the inhibitor of class I and II histone deacetylase (HDAC), trichostatin A, was able to abolish the MGO effect on miR-190a expression, suggesting HDAC involvement. Consistent with previous findings proving the role of MGO in insulin-sensitivity and vascular function [ 53 , 55 , 78 ], the rescue of miR-190a levels we observed in MAECs upon the co-treatment with MGO and AG, revealed that MGO-modified proteins are critical in determining MGO-induced down-regulation of miR-190a.…”
Section: Mgo-induced Insulin-resistance: a Link To Endothelial Dyssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, pretreatment of MAECs with the inhibitor of class I and II histone deacetylase (HDAC), trichostatin A, was able to abolish the MGO effect on miR-190a expression, suggesting HDAC involvement. Consistent with previous findings proving the role of MGO in insulin-sensitivity and vascular function [ 53 , 55 , 78 ], the rescue of miR-190a levels we observed in MAECs upon the co-treatment with MGO and AG, revealed that MGO-modified proteins are critical in determining MGO-induced down-regulation of miR-190a.…”
Section: Mgo-induced Insulin-resistance: a Link To Endothelial Dyssupporting
confidence: 92%
“…This effect is attenuated by the MGO scavengers aminoguanidine (AG) and N -acetyl-cisteine (NAC) [ 52 ], via the inhibition of NADPH oxidase [ 53 ], and is prevented by Glo1 over-expression [ 54 ]. A protective effect of anti-oxidants such as polyphenols has been reported to prevent MGO-dependent impairment of NO release, improving endothelium-mediated relaxation in mouse corpora cavernosa [ 55 ]. A proposed mechanism by which MGO increases reactive oxygen species (ROS), promoting the apoptotic process, involves the reduced transcription of the cytoprotective protein thioredoxin [ 56 ].…”
Section: Effect Of Mgo Accumulation On Vascular Functionmentioning
confidence: 99%
“…EDHF requires triggering by the hyperpolarization of endothelium to be activated. Some papers have reported on the significance of EDHF to endothelium-dependent relaxation which is compromised due to endothelial dysfunction in streptozotocin (STZ)-induced rats [17, 21, 22]. As we have known, KCa3.1 mediates the hyperpolarization of endothelium, and is considered to be critical in initializing EDHF–dilator responses in endothelium-dependent relaxation [18, 23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical trial was conducted with 42 healthy young male Japanese volunteers in Kumamoto, Japan. The following inclusion criteria were used for recruitment: (1) men over 20 years of age, (2) having no history of smoking and (3) having no history of diseases that alter the metabolism and/or excretion of drugs (such as gastroenterological, cardiovascular, pulmonary or hepatic diseases). In addition, the following exclusion criteria were applied: (1) a history of allergy to any foods and drugs, (2) eating functional foods routinely involved in the metabolism of glucose and/or lipids, (3) drinking red wine routinely, (4) having taken part in another clinical trial within three months and (5) taking any internal medication within one week before the start of the clinical trial through the end of the clinical trial.…”
Section: Participants and Clinical Trial Designmentioning
confidence: 99%